ACCUMULATION AND DISTRIBUTION OF OXYTETRACYCLINE AND CHLORTETRACYCLINE IN TOBACCO SEEDLINGS AND THEIR EFFECTS ON GROWTH - X. J. Wang; Y.J. Wang; J.W. Nian; S.W. Liu; Y.H. Zhang; Y.S. Xia; F. Wang; L.F. Wang; R.R. Liu; X.L. Liao; L.F. Zhao; C. Xia; et al. (Journal of Animal and Plant Sciences, 2022)
The accumulation and distribution of oxytetracycline (OTC) and chlortetracycline (CTC) in tobacco seedlings, and their effects on tobacco seedling growth, were studied using the floating seedling method in greenhouse conditions. Results showed that both OTC and CTC could inhibit the growth of tobacco seedlings, and inhibition effects were greater at higher concentrations. Compared with controlling tobacco seedlings treated with the highest concentration T4 (100 mg/L), the root length and root fresh weight in OTC treatment group decreased by 39% and 53%. The length and fresh weight of stem decreased by 34% and 39%. The maximum leaf area and fresh leaf weight decreased by 34% and 46%. The root length and fresh weight in CTC treatment group decreased by 37% and 54%. The length and fresh weight of stem decreased by 53% and 62%. The maximum leaf area and fresh leaf weight were reduced by 59% and 70%. The higher the concentration of antibiotics in the nutrient solution, the higher the accumulation of antibiotics in each tissue of the tobacco seedlings, and accumulation increased significantly from 2 to 80 μg/g over time (7-20 days). And accumulation in leaves (5 to 60, 5 to 80 μg/g respectively) was greater than that in roots (3 to 30, 3 to 15 μg/g respectively) and stems (2 to 25, 2 to 25 μg/g respectively), and CTC inhibited tobacco seedlings more than OTC. The above mentioned two kinds of antibiotic have an effect on tobacco seedling.
Keywords: accumulation; chlortetracycline; growth; oxytetracycline; seedling; tobacco